2018
DOI: 10.1186/s13007-018-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing virus-induced gene silencing at the cellular level with in situ multimodal imaging

Abstract: BackgroundReverse genetic strategies, such as virus-induced gene silencing, are powerful techniques to study gene function. Currently, there are few tools to study the spatial dependence of the consequences of gene silencing at the cellular level.ResultsWe report the use of multimodal Raman and mass spectrometry imaging to study the cellular-level biochemical changes that occur from silencing the phytoene desaturase (pds) gene using a Foxtail mosaic virus (FoMV) vector in maize leaves. The multimodal imaging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Instead, the co‐existence of multiple phenotypes in the same sample facilitates the quantitative comparison of different phenotypes, because the intersample variations and batch effects are eliminated. Burkhow and colleagues (Burkhow et al ., 2018) spatially characterised the biochemical changes in maize leaves following VIGS‐based silencing using multimodal Raman and MALDI imaging. In a similar manner, by combining VIGS, MALDI imaging and LC‐MS we studied GAME31, a 2‐oxoglutarate dependent dioxygenase, catalysing the hydroxylation of α ‐tomatine to hydroxytomatine in the tomato esculeoside A biosynthetic pathway (Cárdenas et al ., 2019) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the co‐existence of multiple phenotypes in the same sample facilitates the quantitative comparison of different phenotypes, because the intersample variations and batch effects are eliminated. Burkhow and colleagues (Burkhow et al ., 2018) spatially characterised the biochemical changes in maize leaves following VIGS‐based silencing using multimodal Raman and MALDI imaging. In a similar manner, by combining VIGS, MALDI imaging and LC‐MS we studied GAME31, a 2‐oxoglutarate dependent dioxygenase, catalysing the hydroxylation of α ‐tomatine to hydroxytomatine in the tomato esculeoside A biosynthetic pathway (Cárdenas et al ., 2019) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman described the spatial distribution of carotenoids, but due to the lack of Raman signal to detect phytoenes, SALDI was chosen to monitor phytoene accumulation when they silenced the chosen gene. 6 In another study, combined information from SERS and LA-ICP-MS demonstrated that hybrid nanoparticles penetrate fibroblast cells differently from standard silica nanoparticles. 14 The SERS spectra reflected the interaction of several amino acids of the side chains of proteins with the nanoparticles’ surface, while LA-ICP images revealed the cellular uptake of silica nanoparticles with a silver core by monitoring the stable isotope 107 Ag.…”
Section: Advantages Of Multimodal Imagingmentioning
confidence: 99%
“…MSI and VSI can be combined to overcome the limitations of one technique and complementing it by the advantages of the other. This combination has been applied in various imaging studies (as illustrated in Table S1 in the Supporting Information): animal brains (mouse, ,, rat, , and hamster), cell cultures, , bacterial colonies, ,, liver metabolism, , cancerous tissues, ,, fingermarks, and even plants (perennial grass and maize leaves). Label-free multimodal imaging is a new holistic approach which will impact analytical chemistry, especially the “omics” sciences, for two main reasons: (1) the imaging techniques provide complementary information that identifies molecules and validates results and (2) the spatial and spectral information have boosted value.…”
Section: Advantages Of Multimodal Imagingmentioning
confidence: 99%
See 2 more Smart Citations